Extracellular vesicles: A new paradigm in understanding, diagnosing and treating neurodegenerative disease - Dar, Ghulam Hassan; Badierah, Raied; Nathan, Erica G.; Bhat, Mohmad Abass; Dar, Abid Hamid; Redwan, Elrashdy M. (Frontiers in aging neuroscience, 2022)
Neurodegenerative disorders (NDs) are becoming one of the leading causes of disability and death across the globe due to lack of timely preventions and treatments. Concurrently, intensive research efforts are being carried out to understand the etiology of these age-dependent disorders. Extracellular vesicles (EVs)—biological nanoparticles released by cells—are gaining tremendous attention in understanding their role in pathogenesis and progression of NDs. EVs have been found to transmit pathogenic proteins of NDs between neurons. Moreover, the ability of EVs to exquisitely surmount natural biological barriers, including blood-brain barrier and in vivo safety has generated interest in exploring them as potential biomarkers and function as natural delivery vehicles of drugs to the central nervous system. However, limited knowledge of EV biogenesis, their heterogeneity and lack of adequate isolation and analysis tools have hampered their therapeutic potential. In this review, we cover the recent advances in understanding the role of EVs in neurodegeneration and address their role as biomarkers and delivery vehicles to the brain.